PENYULUHAN TENTANGPENANGANANLIMBAH RUMAHTANGGA - AF. Junaedi (Asian Journal of Innovation and Entrepreneurship, 2014)
Everyday In our daily we need clean water for drinking, cooking, bathing, washingand other interests, therefore as a human being who cares about the of all living beings,it is our task to prevent and overcome the problem of water pollution by substanceshazardous household waste mainly from one water used to wash (soaps and detergents).Counseling is done so that people know the impact caused by waste soap anddetergents, as well as how a solution to solve water pollution by waste used washing. Sothat people are able to manage wastes produced by their daily activities and can bebeneficial for their continued existence in the future.